2020
DOI: 10.1590/s0100-83582020380100027
|View full text |Cite
|
Sign up to set email alerts
|

Germination Ecology of Ivy-Leaved Morning-Glory: an Invasive Weed in Soybean Fields, Iran

Abstract: Ivy-leaved morning-glory (Ipomoea hederacea Jacq.) is an exotic species that is becoming an increasing problem in soybean fields of Golestan province, Iran. Because little information is available on the biology of this weed species in Iran, experiments were conducted to investigate the effects of different factors on seed germination and emergence of Ivy-leaved morning-glory. Maximum germination occurred at constant temperature of 20 oC (82%) and alternating temperature of 15/25 oC (94%). Germination was redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Additionally, in agreement with the results shown here, high germination percentages under salt stress conditions were found in this species [65,66], as in others of this genus [67,68]. A comparative study on several environmental constraints in I. purpurea revealed that germination was more affected by temperature than by salinity and seedling emergence by flooding and burial depths of over 13 cm [69]. The two species analysed here had similar germination patterns and percentages, except germination at −0.88 MPa osmotic potential in I. purpurea, which was more affected by stress than I. tricolor.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, in agreement with the results shown here, high germination percentages under salt stress conditions were found in this species [65,66], as in others of this genus [67,68]. A comparative study on several environmental constraints in I. purpurea revealed that germination was more affected by temperature than by salinity and seedling emergence by flooding and burial depths of over 13 cm [69]. The two species analysed here had similar germination patterns and percentages, except germination at −0.88 MPa osmotic potential in I. purpurea, which was more affected by stress than I. tricolor.…”
Section: Discussionsupporting
confidence: 92%
“…integriuscula A. Gray) (Gomes et al 1978; Siahmarguee et al 2020). We found a significant number of seeds (47%) emerged from the 8-cm burial depth, and we suggest that shallow burial of seeds through light tillage to reduce I. lonchophylla density may not significantly improve control of this species.…”
Section: Resultsmentioning
confidence: 99%
“…was severely reduced as a result of exposure to high temperatures. The maximum germination percentage of this species was halved at a temperature of 119 °C, and no germination was observed at temperatures higher than 130 °C (Siahmarguee et al, 2020). Sohrabi et al (2016) reported that the germination of Cucumis melo L. is inhibited when the seeds are subjected to long periods of heat at 90 °C.…”
Section: Response Of Geranium Dissectum Seeds To High Temperaturesmentioning
confidence: 98%
“…There were three pots per treatment, and three bags were placed in each pot. The pots containing the seeds were placed inside larger plastic pots (20 cm diameter and 30 cm depth) to maintain 3 cm water above the soil (Siahmarguee et al, 2020). The bags were extracted from pots 0 (control), 2, 5, 10, 15, 20, and 30 days after burial.…”
Section: Response Of Geranium Dissectum Seeds To Salinity Stressmentioning
confidence: 99%